Factors associated with preventive behavior toward COVID-19 infection among African immigrants in Kuala lumpur - Uzoma, Uche Faith; Abdul Manaf, Rosliza; Mokhtar, Siti Aisah; Dapari, Rahmat (Human Resources Management Academic Research Society (HRMARS), 2024)
The study examines the factors associated with preventive behavior toward COVID-19 infection among African immigrants in Kuala Lumpur. The study employed a cross-sectional study carried out on 445 African immigrants. Data were collected using an online Google form and were analyzed using the statistical tool (SPSS 25.0). Pearson Chi-square test of independence and Multiple Regression were used to analyze the data. The findings of the descriptive analysis revealed that the level of education and preventive behavior were good. However, the level of past COVID-19 history was low. therefore, all the variables significantly contributed to preventive behavior among immigrants. The study revealed that the level of education has the highest significant contribution to preventive behavior among immigrants. The study recommended among others, that to minimize the limitation of self-reporting data, further study is required to adopt a qualitative research technique.